2015
DOI: 10.1007/s12070-015-0867-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary Endonasal DCR Without Stent: Our Experience and Case Series Analysis

Abstract: Endonasal dacryocystorhinostomy is widely accepted and effective treatment option for nasolacrimal duct obstruction. It can be done with or without the use of stents. This study was carried out to evaluate the results of endonasal DCR surgery and to access efficacy of this procedure without stenting. This is a prospective clinical study conducted in Departments of ENT and Ophthalmology, L.N. Medical College and J.K. Hospital, Bhopal from October 2008 to April 2012. A total of 90 patients with epiphora as evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Raghuwanshi et al conducted a prospective study with 90 patients who had epiphora due to NLD obstruction and were treated with endonasal DCR without stent during a three-year period. Overall, the outcomes were deemed satisfactory (88.88 percent success rate) [11].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Raghuwanshi et al conducted a prospective study with 90 patients who had epiphora due to NLD obstruction and were treated with endonasal DCR without stent during a three-year period. Overall, the outcomes were deemed satisfactory (88.88 percent success rate) [11].…”
Section: Discussionmentioning
confidence: 88%
“…Without the use of a stent, the overall results were judged to be satisfactory (88.88) percent success rate. By avoiding the use of a stent, not only was the expense of the treatment reduced, but it also reduced the patient's anxiety and the need for follow-up visits from far-ung rural places [11].…”
Section: Discussionmentioning
confidence: 99%
“…There are minor intra and post -operative complications among all primary and revision EDCR occurred in 13 patients and managed conservative without interference where itra nasal synechia occurred in 5 patients, eye and check bruises in 6 patients, stent fallen out in 3 patients , 4 patients with nostril burn and intranasal synechia with the stent fallen out in one patient in revision operations as presented in table [2]. Only one major complication which is orbital penetration, with orbital fat exposure was occurred in one patient in primary EDCR and didn't occur in revision EDCR as as presented in table [2]. The failure has occurred as a result of post-operative scar at the operation site ,associated septal deviation, neo bone formation with osteogenesis , failure in locating the lacrimal sac, and intra nasal synechia, which was corrected in the revision surgery where septoplasty ,release and cut of intra nasal synechia were done with good results as presented in table [3].…”
Section: Resultsmentioning
confidence: 97%
“…The rate of success was 86.7% and the failure rate were occurred in 5 endoscopic DCR 13.3%.The failed 5 eyes undergoing revision endoscopic DCR, and four eyes were improved as presented in table [1]. There are minor intra and post -operative complications among all primary and revision EDCR occurred in 13 patients and managed conservative without interference where itra nasal synechia occurred in 5 patients, eye and check bruises in 6 patients, stent fallen out in 3 patients , 4 patients with nostril burn and intranasal synechia with the stent fallen out in one patient in revision operations as presented in table [2]. Only one major complication which is orbital penetration, with orbital fat exposure was occurred in one patient in primary EDCR and didn't occur in revision EDCR as as presented in table [2].…”
Section: Resultsmentioning
confidence: 99%
“…All three had complete relief of epiphora till 1-year follow-up. A study also reported septoplasty / additional nasal procedure in 5.55% of their patients undergoing endo DCR 18 .…”
Section: Discussionmentioning
confidence: 93%